Fabrication and Analysis of Denture Plate Using Single Point Incremental Sheet Forming - Saad, Hassan; M. Shammari, Ahmed Z.; AlKareem, Salah S. Abed (Al-Khwarizmi Engineering Journal, 2023)
Incremental sheet forming (ISF) is a metal forming technology in which small incremental deformations determine the final shape. The sheet is deformed by a hemispherical tool that follows the required shape contour to deform the sheet into the desired geometry. In this study, single point incremental sheet forming (SPIF) has been implemented in dentistry to manufacture a denture plate using two types of stainless steel, 304 and 316L, with an initial thickness of 0.5mm and 0.8mm, respectively. Stainless steel was selected due to its biocompatibility and reasonable cost. A three-dimensional (3D) analysis procedure was conducted to evaluate the manufactured part’s geometrical accuracy and thickness distribution. The obtained results confirm the capability of SPIF to produce thin-walled biomedical components with satisfactory dimensional accuracy, as geometrical deviations between the developed and the actual models are predominantly in the range of ±0.25mm.